2015
DOI: 10.1021/acs.jmedchem.5b00930
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Reactivities of 2-Furylquinolines: Ubiquitous Scaffolds in Common High-Throughput Screening Libraries

Abstract: High-throughput screening (HTS) was employed to discover APOBEC3G inhibitors and multiple 2-furylquinolines (e.g., 1) were found. Dose-response assays with 1 from the HTS sample, as well as commercial material, yielded similar confirmatory results. Interestingly, freshly synthesized and DMSO-solubilized 1 was inactive. Repeated screening of the DMSO aliquot of synthesized 1 revealed increasing APOBEC3G inhibitory activity with age, suggesting 1 decomposes into an active inhibitor. Laboratory aging of 1 followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 47 publications
2
23
0
Order By: Relevance
“…Interestingly, in this study three of the five initial hits identified were found to inhibit the RGS17-G␣ o interaction through decomposition products. This finding and previous work from Olson et al (111) indicate the decomposition potential for compounds containing furan functionalities in chemical library storage and usage conditions (108). This example highlights the often-repeated cautionary tale of chemical compound library stability and the critical need for structural verification of initial hit compounds (109).…”
Section: Efforts In Rgs Drug Discoverysupporting
confidence: 66%
“…Interestingly, in this study three of the five initial hits identified were found to inhibit the RGS17-G␣ o interaction through decomposition products. This finding and previous work from Olson et al (111) indicate the decomposition potential for compounds containing furan functionalities in chemical library storage and usage conditions (108). This example highlights the often-repeated cautionary tale of chemical compound library stability and the critical need for structural verification of initial hit compounds (109).…”
Section: Efforts In Rgs Drug Discoverysupporting
confidence: 66%
“…Two of these transformations result in the formation of α,β unsaturations through hydrolytic opening of the endoperoxide resulting in the formation of fumarate moieties. 31…”
Section: Resultsmentioning
confidence: 99%
“…A recent report by Olson et al detailed the identification of a chemical structure prone to instability in screening libraries. 31 Additionally, these authors found that this chemical structure was enriched in screening libraries. Therefore, it seems in the best interest of the field to identify compound structures prone to instability to prevent the misallocation of resources toward these chemical entities.…”
Section: Introductionmentioning
confidence: 99%
“…Compound A is an isoxazole with a furan ring in the 2-position. It has been reported that furans tend to undergo oxidative decomposition in air (49,50). To avoid such undesirable properties, three analogues of compound A in which the furan ring was replaced with a methoxy phenyl group were designed, synthesized, and tested for their ability to block HSV-1 infection.…”
Section: Identification Of Hts Hitsmentioning
confidence: 99%